ANALISIS MODAL KERJA TERHADAP SISA HASIL USAHA PADA PNPM SIMPAN PEREMPUAN DESA KERUJON - Yansahrita Yansahrita; Wahyu Haryo Yudanto (Jurnal Signaling, 2019)
This study aims to analyze the effect of working capital on residual proceeds (SHU) on PNPM Savings and Loans for Semendawai Tribe III in East OKU Regency. The liquidity level of PNPM Savings and Loans for the Kerujon Village in Semendawai Sub-District III of East OKU Regency from 2016-2018 experienced a fluctuating situation and even tended to decline. The PNPM Savings and Loans Women's liquidity level in Kerujon Village can be used as a basis for evaluation in the coming years, where in 2016 the current ratio is 202%, which means that every current debt is Rp. 1.00 guaranteed by current assets of Rp. 2.0%. If viewed from the level of activity based on Woring Capital Turn Over (WCTO) in the form of turnover of elements of working capital, it is in a fluctuating position and worsens with a still low turnover rate. Based on the results of the study it can be seen that the amount of funds is unemployed so that it can be proven that the management of working capital in PNPM Savings and Loans in the Village of Kerujon is less optimum.